Featured Article: Interpersonal Stressors and Resources as Predictors of Adolescent Adjustment Following Traumatic Brain Injury. (29th March 2018) - Lantagne, Ann; Peterson, Robin L; Kirkwood, Michael W; Taylor, H Gerry; Stancin, Terry; Yeates, Keith Owen; Wade, Shari L
Abstract: Objective: The present study sought to examine adolescents' perceptions of their interpersonal stressors and resources across parent, sibling, friend, and school relationships, and the longitudinal associations with self-reported adjustment after traumatic brain injury (TBI) over a 12-month period. Methods: We examined the main effects of stressors and resources on internalizing and externalizing symptoms in 152 adolescents who had sustained complicated mild-to-severe TBI. We also investigated the conjoint effects of stressors and resources and the moderating effects of TBI severity with stressors and resources on outcomes. Results: High stressors consistently predicted worse adjustment. High resources were generally only associated with fewer internalizing symptoms. Main effects were qualified by interactions between school stressors and resources in predicting externalizing symptoms and between friend stressors and resources in predicting internalizing and externalizing symptoms. For school stressors, the effects of resources on externalizing symptoms functioned as a buffer. In comparison, the buffering effects of friend resources on internalizing and externalizing symptoms disappeared at moderate-to-high levels of friend stress. Moderating effects of TBI severity were also observed, such that as family resources increased, only adolescents with complicated mild-to-moderate TBI, but not those with severe TBI, experienced decreases in internalizing and eternalizing symptoms. Conclusion: Interpersonal stressors and social support have important implications for adolescent adjustment after TBI. Adolescents with low levels of school resources, with high levels of friend stress, and who sustain severe TBI are at greatest risk for difficulties with adjustment.